2004
DOI: 10.1086/426028
|View full text |Cite
|
Sign up to set email alerts
|

Reaching Stability in Community-Acquired Pneumonia: The Effects of the Severity of Disease, Treatment, and the Characteristics of Patients

Abstract: Some characteristics of CAP are useful at the time of hospital admission to identify patients who will need a longer hospital stay to reach clinical stability. Empirical treatment that follows guidelines is associated with earlier clinical stability. Complications and treatment failure delay clinical stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
0
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 28 publications
4
89
0
11
Order By: Relevance
“…dyspnea, confusion) may predict NRP. 16 Except for former smoking history, myalgia, respiratory rate and pulse oximetry readings (in those for whom this data was recorded), there were no differences in presenting signs, symptoms and comorbid conditions between cases and controls in our study. Nonetheless, cases received more diagnostic tests at the first visit.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…dyspnea, confusion) may predict NRP. 16 Except for former smoking history, myalgia, respiratory rate and pulse oximetry readings (in those for whom this data was recorded), there were no differences in presenting signs, symptoms and comorbid conditions between cases and controls in our study. Nonetheless, cases received more diagnostic tests at the first visit.…”
Section: Discussionmentioning
confidence: 47%
“…21 Our choice of a 4-day window of antibiotic treatment in which there is no further deterioration of vital signs, symptoms or clinical findings is consistent with a prospective study of hospitalized CAP patients by the Menendez group, which observed a median of 4 days of antibiotic treatment to clinical stability using criteria similar to Halm. 16 Additionally, others have defined NRP in hospitalized CAP patients as those with lack of response after 3 to 4 days of appropriate antibiotic treatment, often with clinical deterioration. 7,8,9,17 The second portion of our definition of NRP, 10 days of antibiotic therapy without improvement, is consistent with the observation that 90% of pneumonia-related hospitalizations in a cohort of 944 CAP patients who were treated as outpatients occurred within 10 days of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Una rapidez excesiva de administrar anti- bióticos conllevaría a tratar procesos clínicos probables de neumonía sin evidencia de la misma. La mejoría del proceso clínico no está solamente en ese tiempo de primera dosis, sino en los riesgos de base y los cuidados posteriores que influyen decisivamente (12,16). En nuestro estudio se administran antibióticos, en 6,6 horas desde la llegada a puerta; que está entre la 8 y las 4 horas de la referencias descritas.…”
Section: Resultsunclassified